The effect of resistance band training on developing thigh flexor and extensor muscles, and on the values of some physical and biomechanical variables, and on the performance of the 200-meter sprint for young people. - Kamel, L.Dr. Nawfal Abdul Hussein (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in highlighting the significance of the thigh muscles, given their crucial role in improving the performance of our runners and enabling them to achieve significant results in the men's 200-meter sprint. The research problem stems from the researcher's experience in athletics as a coach of the national team in sprint and hurdle events. He observed the inability of our runners to compete with their world-class counterparts in this discipline, and the considerable gap between our athletes and the international level. The researcher attributes this to the lack of modern methods for developing physical strength, particularly in the thigh flexor and extensor muscles. Therefore, the researcher utilized resistance bands as a safe method to achieve this goal. The study aimed to design exercises using resistance bands for the thigh flexor and extensor muscles and to identify the effect of these exercises on certain physical and biomechanical variables and on 200-meter sprint performance. The researcher adopted the experimental method using equivalent groups, as it was the most suitable means to obtain the most accurate data on a sample of Basra's youth sprinters in the 200-meter race. Through pre- and post-tests of the two research groups, the researcher concluded that the proposed exercises had a positive effect on the development of the experimental group, as indicated by the research variables and performance. Furthermore, the exercises prepared using resistance band training improved the technical running performance of the research group, as indicated by the biomechanical research variables. Based on the research results, the researcher recommends adopting the proposed exercises due to their positive impact on improving athletes' efficiency and performance. The researcher also recommends focusing on developing the thigh extensor and flexor muscles, given their crucial importance in short-distance running in particular and running in general.
Keywords: Training with resistance bands; biomechanical variations